Epigenetics in aquaculture – the last frontier. (18th October 2017) - Granada, Luana; Lemos, Marco F.L.; Cabral, Henrique N.; Bossier, Peter; Novais, Sara C.
Abstract: Aquaculture production is expanding rapidly around the world. To tackle rising production and species diversity issues, innovations in the field of aquaculture feeds, breeding, disease management and other improvements must be addressed. In this framework, the study of epigenetic mechanisms behind different aquaculture rearing processes presents great opportunities. The transcriptional impact of epigenetic modifications, triggered by environmental stimuli, has been shown to influence the organism's phenotype. Therefore, understanding the environmental‐induced epigenetic markers related to disease resistance or other economically important traits will allow the establishment of favourable breeding conditions with increased economical revenue. Several studies have shown epigenetic effects in various species, induced by different rearing conditions, with benefits for the organisms and evidences for heritability of the acquired adaptive phenotypic traits across generations, making these studies even more relevant in a production context. These studies have demonstrated the great potential of epigenetics to positively induce disease resistance, stress tolerance and attain better sex ratios in the aquatic organism. Also, in the field of nutritional epigenetics, the possibility of early nutritional programming to improve the performance of broodstock or even the long‐term performance of their progeny has been suggested. In sum, an increased understanding of epigenetic mechanisms in economically important species, and the epigenetic markers leading to the most favourable phenotypic traits, will contribute to the expansion of economically viable commercial aquaculture industries. The major epigenetic mechanisms and respective analysis methods, as well as the state of the art and potential applications in aquaculture, are addressed in this review.